1984
DOI: 10.1111/j.1471-0528.1984.tb05916.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diabetes and neonatal respiratory distress. I. Maturation of fetal surfactant

Abstract: summary The phospholipid composition of amniotic fluid samples from 30 normal patients and 44 diabetic patients over the last 10 weeks of pregnancy was studied. Higher levels of phosphatidylcholine (PC) and phosphatidylinositol (PI) were found in diabetic pregnancies where there was excellent glucose control. These differences were statistically significant at 34–36 weeks. Phosphatidylglycerol (PG) aeared significantly earlier in the well controlled diabetic pregnancies. but even in the poorly controlled diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Despite attention to all these measures, macrosomia will still occur but should not be associated with significant perinatal complications if the patient has achieved good glycemic control in the latter half of pregnancy and if neonatal hypoglycemia is rapidly detected and corrected. Even if good glycemic control in pregnancy will not guarantee the birth of a nonmacrosomic infant, there is such compelling evidence that meticulous diabetic control reduces perinatal morbidity and mortality that euglycemia remains the therapeutic aim for every diabetic patient during pregnancy (8,19,(27)(28)(29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
“…Despite attention to all these measures, macrosomia will still occur but should not be associated with significant perinatal complications if the patient has achieved good glycemic control in the latter half of pregnancy and if neonatal hypoglycemia is rapidly detected and corrected. Even if good glycemic control in pregnancy will not guarantee the birth of a nonmacrosomic infant, there is such compelling evidence that meticulous diabetic control reduces perinatal morbidity and mortality that euglycemia remains the therapeutic aim for every diabetic patient during pregnancy (8,19,(27)(28)(29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
“…It may be that it is a manifestation of the normal surfactant maturation process, which normally commences, on average, at 34 weeks [1], and which has been unaffected by the membrane rupture. Studies on plate let-activating factor (PAF) in amniotic fluid have suggested that the two processes might be commonly related [10].…”
Section: Discussionmentioning
confidence: 99%
“…Onemillilitre aliquots of each sample were subjected to a standard lipid extraction technique [8]. The phospho lipid content of the lipid extract was then assayed using a method previously described [1]. The concen trations of three surfactant phospholipids were mea sured: phosphatidylcholine (PC), phosphatidylinosi tol (PI) and phosphatidylglycerol (PG) together with the concentration of sphingomyelin (SM).…”
Section: Laboratory' Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, the lecithin: sphingomyelin ratio of 2 2 and the presence of phosphatidylglycerol in amniotic fluid (1 1, 12) suggests fetal lung maturity. However, the infants in full term diabetic pregnancies are at increased risk of developing RDS, despite normal lecithin: sphingomyelin ratio of 2 2 (13)(14)(15). Some reports have shown that the level of SP-A is reduced in amniotic fluid of pregnant diabetic women (16,17), suggesting that decreased SP-A contributes to the increased incidence of RDS in infants of diabetic mothers.…”
mentioning
confidence: 99%